From Family to Digital Space: Reconstructing Parental ‎Authority in Islamic Character Education among Millennial ‎Families - Kunaepi, Aang; Yusuf Isnan Setiawan, Akhmad (JPI: Jurnal Pustaka Indonesia, 2026)
This study examines how digital gaming reshapes parental authority in Islamic character education among millennial families. Using a qualitative case study design, the research was conducted in Wonodadi Village, Plantungan District, Kendal Regency, Central Java, Indonesia, with eleven millennial parents selected purposively. Data were generated through in-depth semi-structured interviews, participant observation, and document analysis and were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings identify a gradual digital authority shift driven by limited parental accompaniment, insufficient supervision after providing digital devices, children’s intensive exposure to online games, and limited parental digital literacy. Parents’ accounts and field observations associated this shift with weaker discipline in religious practice, declining respectful communication with parents, and reduced self-control and responsibility. Parents responded through four adaptive strategies: negotiating rules for device duration and use, rebuilding parent–child emotional bonds, integrating Islamic values into everyday routines, and using digital media selectively as a character-education resource. The study proposes a digital authority shift model in which parental authority is reconstructed through relational presence, value-based mediation, and adaptive digital guidance rather than restriction alone.